RANCANG BANGUN MONITORING POLUSI UDARA BERBASIS ARDUINO - Muhammad Zikri; Rizaldy Khair (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2018)
Air pollution is a condition with air quality becomes damaged and contaminated by substances. Lack of information on air pollution in Medan cause people not to be aware of the increase of air pollution. In this study an Arduino-based air pollution monitoring was made. Use the mq135 sensor to detect CO2 gas. The output of this system is a display on LCD 1602a and led green if the value of 200-300, LED yellow if the value of 301-500, red LED and buzzer flame if the value exceeds 500. The system is expected to be a solution to air pollution in Medan.